Approach and management of congenital cataract: A review article - Parisa Abdi; Zakieh Vahedian; Atefeh Dehghani; Mona Safizadeh; Elias Khalilipour (Tehran University Medical Journal, 2023)
Congenital cataract refers to the presence of any opacity in the lens at birth or during early childhood. Cataracts in children can manifest as unilateral or bilateral, congenital or acquired, with specific inheritance patterns or occurring sporadically. Additionally, the condition can be stable or progressive. Congenital cataracts can be associated with certain systemic diseases, or they may occur in the eye of an otherwise healthy child in isolation. Congenital cataract is one of the main causes of blindness in childhood. According to the report of the World Health Organization in 2001, congenital cataract is responsible for about 5 to 20 percent of cases of childhood blindness in the world based on different geographical regions. Untreated cataract in children leads to a tremendous social, economic and emotional burden for the child, family and society. Common complaints associated with congenital cataracts often include leukocoria (white pupil), reduced vision, a child's inability to track objects up close, light sensitivity leading to eye closure, squinting, the presence of either small eyes (microphthalmos) or large eyes (buphthalmos), strabismus (eye deviation), and abnormal eye movements such as nystagmus. Childhood cataract-related blindness can be cured with early detection and appropriate management. Managing pediatric cataracts is a challenge. Increased intraoperative complications compared to adults, tendency to increase postoperative inflammation, associated with complications such as aphakic glaucoma and persistent fetal vasculature, change in refractive status of the eye, and tendency to develop amblyopia, all complicate the achievement of good vision. Congenital cataract has a good prognosis if it is diagnosed early and surgery is performed before 6 weeks. Factors that may adversely affect the outcome, include the presence of unilateral cataract, presence of nystagmus, strabismus, or any ocular defect such as microphthalmos and PFV. Pediatric cataract surgery has evolved over the years, and with improved knowledge about myopic shift and axial growth, outcomes for these patients have become more predictable. Optimal results depend not only on effective surgery, but also on careful postoperative care and visual rehabilitation. Hence, it is the combined effort of parents, surgeons, anesthesiologists, pediatricians and optometrists that can make the difference.